PERAN ORGANISASI KEAGAMAAN MUHAMMADIYAH DALAM MODERNISASI EKONOMI MASYARAKAT ISLAM DI KOTA PEKANBARU (TAHUN 2017) - Rahman, Hafizur; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Pekanbaru City with the title research of the Role of Muhammadiyah Religious Organization in Modernization Economy of Islamic Society in Pekanbaru City (Year 2017). This study aims to determine the role of religious organizations Muhammadiyah in controlling the modernization of Islamic economics in Pekanbaru City, to analyze the factors driving the role of Muhammadiyah religious organizations in controlling the economic modernization of Islamic societies in Pekanbaru City. And to analyze the factors inhibiting the role of Muhammadiyah religious organizations in controlling the economic modernization of Islamic society in Pekanbaru City. This research is a qualitative research. Subjects in this study amounted to 4 people consisting of general chairman Muhammadiyah Pekanbaru organization, chairman of each charity business Muhammadiyah, general cadres organization and community. Data collection researcher using interview and documentation guides. The results show that Muhamadiyah organization has a role in the context of modernization by providing solutions to the impact of technological development, the development of industrialization, and how to overcome the high level of mobility. In the concept of social change, it is seen that Islamic society is changing due to modernization but has better social change and the factors that influence the role are divided into two, namely internal and external factors. On internal factors if less power cadres, da'i, preachers then Muhammidah organization to add and do training. While external factors to evaluate the existing leaders so as to find out what solutions to improve the goal of quality development program of the people evenly.Keywords: Role, Organization, Religious Muhammadiyah, Modernization